The Effect Of Adding Milkfish Bones On The Chemical Characteristics Of Oyster Mushroom-Based Natural Flavor - Pinctada Putri Pamungkas; Alya Rosita2; Maslukhi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This study aimed to determine the effect of adding milkfish bones on the chemical characteristics of an oyster mushroom-based natural flavor enhancer. The research used a Completely Randomized Design (CRD) with a single factor consisting of five treatment levels: P1 (90:10), P2 (85:15), P3 (80:20), P4 (75:25), and P5 (70:30), with replications. The observed parameters included ash content, protein, calcium, moisture, fat, and glutamic acid. Data were analyzed using ANOVA at a 5% significance level. The results showed that the addition of milkfish bones significantly affected protein, fat, and glutamic acid content, but had no significant effect on moisture and ash content. The highest values of protein (33.33%), fat (6.04%), and glutamic acid (3.74%) were obtained in treatment P5. In addition, calcium content in the selected treatment (P5) reached 868.5 mg/100g. Overall, treatment P5 produced the best chemical characteristics and has potential as a natural flavor enhancer with high nutritional value and strong umami taste.